Setting the stage for family reunification. Issue 4 (6th April 2020) - Harris, Elizabeth; Becerra, Miguel
Abstract: Parents whose children are removed by the child welfare system are generally required to participate in a set of community‐based services as a condition for reunification. Often, these services are provided by outside non‐profit agencies. In this study, the authors analysed data from 27 interviews with parents whose children were removed by child welfare and four focus groups totalling 18 staff from a parent education service provider. The data suggest that while these non‐profit programmes are designed to improve the parental behaviours that led to their child welfare system involvement, staff and parents also describe the programmes as helping them develop a specific performance of self (Goffman, 1956) when interacting with child welfare agencies. This performance ultimately facilitates their capacity to build an effective working relationship with their social workers and thereby negotiate the process of reunifying with their children (Cheng and Lo, 2016; Reich, 2005). In keeping with Goffman's 1956 theory, staff from contracted non‐profit agencies help parents understand what is expected on the child welfare stage. This impression management is a critical skill for system‐involved parents, who often come from a class and cultural background that differs from those who work professionally in child welfare settings.